Speculative dynamics in a time-delay model of asset prices - Dibeh, Ghassan (2005)
In this paper, a time-delay model of speculative asset markets is developed to investigate the effect of time delays on the dynamics of asset prices. The basic model investigates the effect of time delays in the chartists expectations function on the deviation of asset prices from their fundamental value. A nonlinear model is then solved showing that limit cycles may exist explaining the persistence of these deviations in speculative markets. Time delays are shown to have an effect on the generation of limit cycles. The model is also extended to include endogenous wealth dynamics. Solutions to the model show that time delays affect the time evolution of the chartists and fundamentalists share of wealth.